Beyond Deterrence: Behavioral Economics and Institutional Trust in Tax Compliance (European Journal of Behavioral Sciences, 2025)
This paper integrates behavioral economic frameworks with comparative institutional analysis to explain tax compliance beyond traditional deterrence approaches. Drawing on empirical evidence from Scandinavian countries (Sweden, Norway, Denmark), characterized by high trust and voluntary compliance, and contrasting them with low trust contexts (Israel and Greece), the study highlights the critical roles of intrinsic motivations, social norms, and institutional trust in shaping taxpayer behavior. The findings extend the "slippery slope" framework by demonstrating how institutional legitimacy fosters voluntary compliance more effectively than coercive enforcement. Practical insights for policymakers include enhancing transparency, civic engagement, procedural fairness, and targeted behavioral nudges.